THE DEVELOPMENT OF THE REGIONS AND THE GENESIS OF THEORIES OF REGIONAL ECONOMY - A. Nazarov (Вестник университета)
The article is devoted to the formation and development of regional economy theory in Russia and abroad. From the standpoint of a systemic approach it the basic concept of the specialization of the regional economy and the most efficient allocation of production. Dana systematize the stages of development of regional economics.